Tingkat Kepuasan Pasien terhadap Kualitas Pelayanan Kefarmasian di Apotek Klinik X Gading Serpong Tangerang - Muhajri Agusfina; Renatalia Fika; Ainun Naim; Asima Sihol Marito Marpaung (Journal Pharma Saintika, 2024)
Patient satisfaction survey is one of the evaluation methods that can be used to assess the quality of clinical pharmacy services. This study aims to measure the satisfaction of respondents/patients with pharmaceutical services at the X Gading Serpong Tangerang Clinic Pharmacy for the period December to March. This type of research is qualitative descriptive. The number of samples is 50 respondents, sampling using purposive sampling techniques, the research instrument is a questionnaire sheet using a manual method. The questions in the questionnaire are compiled based on the laws and regulations in force in Indonesia regarding pharmaceutical service standards in health centers, pharmacies, clinics and hospitals. The questionnaire statements are divided into five dimensions of service quality, namely the reliability dimension, the responsiveness dimension, the empathy dimension, the Facilities and Infrastructure dimension, and the Assurance dimension. The number of questions is 22 questions, 6 questions on the reliability dimension, 3 questions on the responsiveness dimension, 4 questions on the empathy dimension, 5 questions on the Facilities and Infrastructure dimension, and 4 questions on the assurance dimension. The average value based on the Five Dimensions: the level of patient or respondent satisfaction can be seen from each dimension, the Reliability Dimension is 88%, the Responsiveness Dimension is 87%, the Empathy Dimension is 92% very satisfied, the Facilities and Infrastructure Dimension is 87% very satisfied, the Assurance Dimension is 91% very satisfied.